Pengembangan Aplikasi E-Voting Untuk Pemilihan RT/RW Menggunakan Metode Waterfall di Lingkungan Masyarakat Daerah Macan Lindungan Bukit - Agung Setiaji; Tata Sutabri; Kemas Muhammad Wahyu Hidayat (Jurnal Nasional Ilmu Komputer, 2023)
This research focused on RT.003 RW.003 in Macan Lindungan Bukit area. The RT.003.RW.003 area is included in Bukit Baru Village, Ilir Barat I District, Macan Lindungan Region. Bukit Baru Village has existed since February 22, 1996. Initially, Bukit Baru Village was the result of the expansion of Bukit Lama Village. Bukit Baru sub-district, especially the RT.003 area, was initially very quiet and deserted because most of the area was swamp, where the population was still very small. Along with the progress of development and the increase in living standards and the success of government, especially RT.003, Bukit Baru Village, it can be said to be developing well. As an area that is still developing towards a developed society area, the selection of RT.003 and RW.003 in this area is still done manually. Where residents are invited to come to the meeting hall to vote, with paper and pens distributed by the committee to choose the candidate for RT/RW chairman. In this research, we will develop an E-Voting application system, which will be implemented in RT.003 in Macan Lindungan area. E-Voting was developed to make it easier for citizens to vote and to know the results quickly. The method used in software development uses the Waterfall system planning method using Unified Modeling Language (UML) and system testing uses black box testing. With the web-based e-voting application development model, residents no longer have to come to the polling place but residents can simply vote from home. The programming language used in developing this e-voting application is Web-based PHP and a database that uses MYSQL. Residents who are voters in RT.003 area will be given a user name and password in the online voting process, and can see the vision and mission platform of RT.003 chairman candidates in the e-voting application. The e-voting system that was built provides an interface that is easy for users to use and offers a data search process and election report results that can be immediately known, compared to manual processes.